The social and personality neuroscience of empathy for pain and touch - Bufalari, Ilaria; Ionta, Silvio (Frontiers in Human Neuroscience, 2013)
First- and third-person experiences of bodily sensations, like pain and touch, recruit overlapping neural networks including sensorimotor, insular, and anterior cingulate cortices. Here we illustrate the peculiar role of these structures in coding the sensory and affective qualities of the observed bodily sensations. Subsequently we show that such neural activity is critically influenced by a range of social, emotional, cognitive factors, and importantly by inter-individual differences in the separate components of empathic traits. Finally we suggest some fundamental issues that social neuroscience has to address for providing a comprehensive knowledge of the behavioral, functional, and anatomical brain correlates of empathy.